2013
DOI: 10.1055/s-0033-1350873
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonale Metastasektomie: Analyse technischer und onkologischer Ergebnisse bei 301 Patienten mit Fokus auf die Laserresektion

Abstract: The number of metastases has an influence on prognosis but seems to be of secondary importance, particularly if complete technical resectability with the aid of the laser is given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 7 publications
0
26
0
Order By: Relevance
“…The mean disease-free interval for all patients was 12.9 months. After a median follow-up period of 27.2 months, 42.5% had experienced a recurrence and 29.2% had died [19]. In a clinical study by Vodicka et al [1] the 5-year survival rate for 87 patients was 38%.…”
Section: Complications and Results After Laser Surgerymentioning
confidence: 97%
See 1 more Smart Citation
“…The mean disease-free interval for all patients was 12.9 months. After a median follow-up period of 27.2 months, 42.5% had experienced a recurrence and 29.2% had died [19]. In a clinical study by Vodicka et al [1] the 5-year survival rate for 87 patients was 38%.…”
Section: Complications and Results After Laser Surgerymentioning
confidence: 97%
“…In another paper, Rolle et al [18] reported that one case of postoperative haemothorax and one prolonged air leak occurred in 100 cases treated surgically. In a retrospective evaluation Osei-Agyemang et al [19] found that between a group treated with conventional surgery versus a group treated with laser surgery, only the rate of postoperatively-occurring pneumonia was markedly increased (11.3% as opposed to 2.9%) [19]. However, the use of lasers has made it possible to successfully treat patients with a large number of lung metastases.…”
Section: Complications and Results After Laser Surgerymentioning
confidence: 99%
“…The Nd:YAG Laser has become indispensable in lung surgery procedures [1]. It is used mainly in the context of open surgical procedures for the resection of lung metastases.…”
Section: Introductionmentioning
confidence: 99%
“…The aim is to perform a non-anatomic resection of all palpable lung metastases in order to preserve the largest possible amount of lung parenchyma [2]. Anatomical lung resections are only carried out when the metastases are located more centrally or have reached a certain size [1]. If the branch of the lobar bronchus exhibits infiltration it even becomes necessary to perform sleeve lobectomy.…”
Section: Introductionmentioning
confidence: 99%
“…In another retrospective study, Osei-Agyemang et al demonstrated that although a higher number of metastases was resected in the laser group, there was no significant benefit in the long-term survival (20).…”
mentioning
confidence: 97%